Pengaruh Penerapan Green Accounting dan Environmental Performance Terhadap Profitabilitas Perusahaan Sektor Healthcare yang Terdaftar di BEI Tahun 2020-2022 - Ahmad Zulkarnain; M. Cholid Mawardi; Junaidi Junaidi (Universitas Islam Malang, 2023)
This study aims to determine the effect of Green Accounting and environmental on profitability in Healthcare companies. This disquisition uses quantitative styles. The sample used in this study is a Green Accounting company for the 2020-2022 period on the main board on the Indonesian Stock Exchange (IDX). The data were anatomized using multiple direct retrogression analysis. Based on data analysis, it shows that: 1. The variables of environmental performance and environmental costs in green account companies in 2020-2022 have a contemporaneous effect on profitability. 2. Environmental performance variables in Healthcare companies in 2020-2022 have no effect on profitability. 3. Environmental cost variables in Healthcare companies in 2020-2022 have a negative effect on profitabilityKeywords: Green accounting, environmental performance, environmental costs.